2. KEPENTINGAN PEMERINTAH NORWEGIA DALAM KERJASAMA PENANGANAN DEFORESTASI DAN DEGRADASI HUTAN DI INDONESIA MELALUI MEKANISME REDD+ - Mesi Fransiska Berutu; Hermini Susiatiningsih; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2016)
The deforestations and forest degradations in Indonesia have a global impact as they havebeen held responsible in increasing the amount of world carbon emissions. Thegovernment of Indonesia actively participates in many efforts combating the problem, oneof which materialiazed throughthe initiation of bilateral cooperation between Norway andIndonesia under the scheme of REDD+ (Reducing from Deforestations and ForestDegradations), where Norway plays role as donor and Indonesia becomes the recipientcountry.This particular cooperation could be well explained by utilizing the approach ofConstrutivism. Following the constructivists’ stand point, the Norwegian action in givingdonor to Indonesia isseen inseparable from Norway’s identity as a ‘green actor’ whoincludes environment as one of the primacies among her foreign policy priorities.